Efficiences idéales et défaillances réelles : une lecture des Lettres persanes - Colas Duflo (Etudes Epistémè)
In the Lettres persanes, Montesquieu gave a striking formulation of the optimum in political philosophy, according to which the 'most perfect government is the one that reaches its goal at the lowest cost' (Letter LXXX). But the narrative tells a different story, one that constantly contrasts the formulation of ideal efficiencies and the reality of waste in all the areas mentioned. What can we think of a narrative philosophy in which the explicit philosophies of efficiency are inseparable from the stories of deficiency? Starting with a commentary on the "standard" formulation of the optimum in Letter LXXX, we will identify as systematically as possible the different formulas that state optima, in the organisation of the seraglio, in religious economy, in the description of political life, by confronting them with the different facets of this narrative of failures, that of Usbek, that of the French monarchy, that of world history. The investigation of the formulations of efficiency and the way in which they are worked on narratively makes it possible to understand how a political philosophy can expose itself as true and at the same time be caught in a sceptical network, which is the very dimension of the narrative. Will we thus be able to propose a solution to the critical conflict about the meaning of the Lettres persanes between the proponents of a philosophical interpretation and the defenders of a carnivalesque reading?